Inflectional Morphemes in Maudy Ayunda’s Book “Dear Tomorrow” - Putri Oktaviani, Ni Wayan; Udayana, I Nyoman; Rajeg, I Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2025)
Abstract—The article aims to find out the types of inflectional morphemes used by the writer in the book, as well as to identify the functions of inflectional morphemes found in the book. The data source was from the self-improvement book entitled “Dear Tomorrow” by Maudy Ayunda. The data was analyzed using the theory of O’Grady and Archibald (2016). Moreover, the data was collected through observation and documentation methods. Descriptive qualitative method in the form of content analysis was used to analyze the data. The analysis was conducted in several stages. First, the O’Grady and Archibald (2016) hypothesis was utilized to identify the types of inflectional morphemes used in the book. Furthermore, the theory of the functions of inflectional morphemes developed by O’Grady and Archibald (2016) was used to analyze the functions of inflectional morphemes. The results of the analysis showed that there were seven out of eight types of inflectional morphemes found in the book. In terms of the functions of inflectional morphemes, it was discovered that seven functions were detected in the data source. Keywords: inflectional morphemes, types of inflectional morphemes, functions of inflectional morphemes